Equações diferenciais de Liénard definidas em zonas - Ruiz, Jeidy Johana Jimenez (2016)
The study under existence and uniqueness of limit cycles of equations systems differential is a very active research topic in the qualitative theory of dynamical systems. In this theme we study this topic in discontinuous dynamic systems. Let’s make this in Liénard differentials equation systems, allowing a line of discontinuity. Furthermore, we present the known method of Averaging firstly in your classic version, that is, for class fields at least C2, we study also to generalized version, to piecewise- smooth dynamical systems. As a result, we use this tool to determine the number of limit cycles that can bifurcate of a planar center, inside the equation Liénard differentials equation class.